KICHIK MAKTAB YOSHIDAGI BOLALAR YUQORI YUZ KO‘RSATKICHINING MORFOMETRIK TAHLILI - Ulug‘bekova, G.J.; Adhamov, Sh.A.; Mamasoliyeva, Sh.A.; Bustanov, Sh.Y. (SCIENCE and SOCIETY, 2024)
In this article, the results of the anthropometric research conducted in order to analyze the upper face index in children of junior school age: to monitor its growth in dynamics, to study the periods of formation, the laws of growth and development (as an example of morphometric indicators obtained from children living in Izboskan district) illuminated.